Paradigm shifts: how electrical stimulation opened up new avenues in science and medicine - Stanley Salmons (European Journal of Translational Myology)
The discovery that skeletal muscle can respond adaptively to use, even to the extent of re-expressing its genome, overturned two paradigms and led to new insights into gene regulation and a variety of clinical applications.